Application of virtual reality technology in football education field - Sun, Q. (Proceedings of First Joint International Pre-Olympic Conference of Sports Science and Sports Engineering. Volume III: Statistics and Managment in Sports., 2008)
As a new emerging technology, virtual reality technology has a wide range of potential applications in various aspects, particularly in educational field. The purpose of this article is to discuss the application of vinual reality technology in football instruction from an educational perspective. The author defines the concept of this technology and generalizes its general features. Meanwhile the author focuses on the application of football instruction as well as the advantages of the technology. Thus he provides certain references in exploring new development of virtual reality technology in physical education.